State of the Art in Separation Science - Samanidou, Victoria (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In this Topical Collection, ten articles (one review and nine research articles) are published in a time span of 2021-2022. All articles are written by experts in the field of Separation Techniques who were invited to contribute to the presentation of the current status in separation science. The authors were invited to answer the questions: What is the state-of-the-art in Separation Sciences? What advances have been reported recently? Last but not least, what are the future perspectives? The Editor and authors hope that the readers will find valuable information in the topic.